2019
DOI: 10.1088/0253-6102/71/3/312
|View full text |Cite
|
Sign up to set email alerts
|

A Modified Gravity Theory: Null Aether

Abstract: General quantum gravity arguments predict that Lorentz symmetry might not hold exactly in nature. This has motivated much interest in Lorentz breaking gravity theories recently. Among such models are vector-tensor theories with preferred direction established at every point of spacetime by a fixed-norm vector field. The dynamical vector field defined in this way is referred to as the “aether”. In this paper, we put forward the idea of a null aether field and introduce, for the first time, the Null Aether Theor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…In this work, we investigated the properties of the black hole solutions found in NAT [35] which is a vector-tensor theory of gravity with the vector field being null and defining the aether field at each point of the spacetime. We first reviewed the Newtonian limit of the theory and showed that the Poisson equation is recovered at the linear order in the gravitation constant G of the theory which, depending on the form of the null vector, is related to the Newton's constant G N by a scaling factor.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this work, we investigated the properties of the black hole solutions found in NAT [35] which is a vector-tensor theory of gravity with the vector field being null and defining the aether field at each point of the spacetime. We first reviewed the Newtonian limit of the theory and showed that the Poisson equation is recovered at the linear order in the gravitation constant G of the theory which, depending on the form of the null vector, is related to the Newton's constant G N by a scaling factor.…”
Section: Resultsmentioning
confidence: 99%
“…v µ = 0) with an arbitrary λ reduces the theory to the usual general relativity; however, this trivial case can be distinguished from the nontrivial aether case by imposing certain initial and boundary conditions on the solutions of the Einstein-Aether equations (4) and (5). (See the discussion in [35].) Since the aether field in NAT is null by construction, one can always introduce a scalar degree of freedom into the theory.…”
Section: Null Aether Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…where ω e and ω ∞ are the electron plasma frequency and the photon frequency measured by an observer at infinity, respectively. The line-element (16) can be rewritten as:…”
Section: B Weak Deflection Angle Of Nat Bh In a Plasma Mediummentioning
confidence: 99%
“…NAT is one of the new vector-tensor theories of modified gravity theory [16]. In this theory, the dynamical vector field acts as the aether and exact spherically symmetric BH solution with charge is possible [17].…”
Section: Introductionmentioning
confidence: 99%